A Review: Potensi Pengembangan Pati Resisten Dengan Modifikasi Autoclaving-cooling Sebagai Pangan Fungsional - Puspawati, Ni Nyoman; Adyeni, Wayan Dewi; Setiarto, R. Haryo Bimo (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 4 (2024): Jurnal ITEPADO - 10.24843/itepa.2024.v13.i04.p10, 2024)
Starch modification is an activity that aims to change the physical or chemical properties of starch as needed, especially to increase the level of resistant starch (RS). One modification technique that has been widely practiced is autoclaving-cooling. The purpose of this review is to evaluate the potential of devekoping resistant starch with autoclaving-cooling modification in root crops and its functional effects. Autoclaving-cooling is a physical modification technique that can produce etrogradable starch, which can reduce starch digestibility and increase resistant starch content. The main functional effect of foods containing resistant starch is that they can be fermented by the microbiota in the colon, which is know as the prebiotic effect. Prebiotics are utilized by probiotic bacteria as selective substrates in metabolism that produce short-chain fatty acids (SCFA). Short-chain fatty acids, especially acetate, propionate, and butyrate, have various effect, including a role in obesity management, diabetes, and liver disease. Keywords: Modification starch, resistant starch, autoclaving-cooling, functional effect.